Autoinducer-2 relieves soil stress-induced dormancy of Bacillus velezensis by modulating sporulation signaling - Qin Xiong; Huihui Zhang; Xia Shu; Xiting Sun; Haichao Feng; Zhihui Xu; Ákos T. Kovács; Ruifu Zhang; Yunpeng Liu (npj Biofilms and Microbiomes)
Abstract The collective behavior of bacteria is regulated by quorum sensing (QS). Autoinducer-2 (AI-2) is a common QS signal that regulates the behavior of both Gram-positive and Gram-negative bacteria. Despite the plethora of processes described to be influenced by AI-2 in diverse Gram-negative bacteria, the AI-2-regulated processes in Bacilli are relatively unexplored. Here, we describe a novel function for AI-2 in Bacillus velezensis SQR9 related to the sporulation. AI-2 inhibited the initiation of sporulation through the phosphatase RapC and the DNA binding regulator ComA. Using biochemistry experiments, we demonstrated that AI-2 interacts with RapC to stimulate its binding to ComA, which leads to an inactive ComA and subsequently a sporulation inhibition. The AI-2 molecule could be shared across species for inhibiting Bacillus sporulation and it also plays the same role in different soil conditions. Our study revealed a novel function and regulatory mechanism of AI-2 in inhibiting sporulation in Bacilli.